The Radiation Sterilization of Ertapenem Sodium in the Solid State - Kilińska, Karolina (Molecules, 2019)
For the first time, the influence of ionising radiation on the physicochemical properties of ertapenem in solid state was studied. During our studies, we evaluated the possibility of applying radiosterilization to obtain sterile ertapenem. Spectroscopic (Fourier Transform Infrared (FT-IR)), thermal (differential scanning calorimetry (DSC), chromatography (High-Performance Liquid Chromatography (HPLC) and HPLC-MS), and X-ray powder diffraction (XRPD) studies shown that irradiation of ertapenem with the 25 kGy, the dose required to achieve sterility, does not change the physicochemical properties of the studied compound. The antimicrobial activity of ertapenem irradiated with the dose of 25 kGy was only reduced for one species. Based on the received results, we can conclude that radiostelization is a promising alternative method of obtaining sterile ertapenem. In our studies, ertapenem was also exposed to e-beam radiation with a dose of 400 kGy. It was determined that two novel degradation products that are structurally differently to degradants formed during hydrolysis and thermolysis.